Why cycling matters for electric mobility: towards diverse, active and sustainable e-mobilities. Issue 1 (2nd January 2018) - Behrendt, Frauke
Abstract: This paper proposes the concept of e-velomobility. E-velomobility covers practices, systems and technologies of electrically-assisted cycling where velomobility's pedal-power combines with e-mobility's battery/motor assistance to propel the rider. The concept draws on research and policies around e-mobility, velomobility and e-bikes. Results of an analysis of qualitative material from a UK trial of e-bikes illustrate how e-velomobility is experienced. The empirical material and the conceptual approach show e-velomobility as a distinct and important form of mobility with implications for research agendas and e-mobility policy. E-velomobility and the more diverse understanding of e-mobility suggested in this paper could support a shift of strategies and policies towards more active and sustainable as well as less expensive modes of e-mobility than the current focus on electric cars.